Sainik school Dehradun: Uttrakhand/ - subhash, Visave Poonam. (SPA Bhopal, 2025)
The project's main goal is to design a Sainik School in Dehradun, Uttarakhand, which combines academic brilliance with military discipline in order to develop future military commanders. The site, which is close to the ancient Tibba Nalapani War Memorial in the Khalanga region, has great cultural and geographical value and presents a chance to design with context and purpose in mind. The need for educational establishments that offer more than just traditional classroom settings is rising. In order to meet this demand, Sainik Schools incorporate discipline, physical training, and patriotic values into regular teaching. In order to create a campus that is not only secure and useful but also motivating, climate-responsive, and context-sensitive, this thesis aims to transform these principles into architectural and spatial form. The design strategy places a strong emphasis on spatial hierarchy, axial planning, and symmetry, which reflects the discipline and order that are essential to military organizations. The Administration, Academic, and Training institutional blocks are positioned strategically around the Parade Ground, which serves as the focal point of the master plan, to strengthen the sense of identity and organization. The design of academic areas, recreational centers, and hostels promotes holistic development while upholding discipline and privacy. In response to Dehradun's climate, local materials and passive design techniques are employed, and the physical form draws influence from the local architectural language to foster a feeling of pride and community. Because of studies that show a connection between outdoor and recreational places and students' physical and mental health, special attention is paid to them. The user experience is intended to empower students by encouraging leadership, independence, and teamwork. While offering comfort and practicality for daily academic and residential life, the spaces are designed to gently emphasize the ideals of routine, teamwork, and resilience. This thesis demonstrates how architectural planning can reinforce institutional values like discipline, leadership, and unity, through a context-responsive and functionally efficient design. The aim is to set a benchmark for future military school campuses by creating a cohesive, inspiring, and resilient learning environment. Keywords: Military Education, Context-Responsive Design, Discipline and Leadership
Keywords: Architecture; India - Uttrakhand; Design strategies; School Infrastructure.